The role of the exchange rate in economic growth: a euro-zone perspective - Ronald MacDonald (National Bank of Belgium, 2000)
In this paper we consider a range of topics which connect exchange rates to the economic growth process. In particular, we first of all outline the basic properties of exchange rates when they are flexible. One key feature of flexible exchange rates is that they are highly volatile and such volatility may affect growth through the channels of trade and investment. These channels are considered in some detail in this paper. We also consider the links between sectoral and aggregate growth and the exchange rate, using the Balassa-Samuelson and Houthakker-Magee-Krugman hypotheses. The main conclusion of the paper is that the current exchange rate arrangements for the euro-zone area, both internal and external, are likely to stimulate economic growth.
Keywords: 330; Wirtschaftswachstum; Wechselkurspolitik; Euro; Flexibler Wechselkurs; EU-Staaten